Teh Herbal Daun Kelakai (Stenochlaena palustris) sebagai Potensi Fitoestrogen Untuk Produksi ASI : Terinspirasi dari Kearifan Lokal Suku Anak Dalam Jambi - Intami, Eprina; Mustakim , Ardi; Rahmadevi, Rahmadevi; Mulyati , Sri (Journal of Pharmaceutical and Sciences, 2026)
This study was conducted in response to the problem of low breast milk production among some breastfeeding mothers, which may adversely affect infant growth and development. One approach to enhancing breast milk production is the utilization of natural substances containing phytoestrogens. Kelakai leaves (Stenochlaena palustris) are a plant traditionally used by the Suku Anak Dalam community as part of local wisdom to support maternal health during the postpartum period. This study aimed to develop kelakai leaf herbal tea as a natural source of phytoestrogens with potential to support increased breast milk production. The research employed a quasi-experimental design using a one-group pre-test and post-test with control group approach, complemented by laboratory analyses including identification of active compounds, simplicia processing, herbal tea formulation, phytochemical screening, and phytoestrogen content analysis. The results demonstrated that kelakai leaves contain flavonoids, saponins, and phytoestrogenic compounds that may contribute to the stimulation of prolactin and oxytocin secretion. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of kelakai herbal tea administration on breast milk production among breastfeeding mothers. Based on these findings, it can be concluded that kelakai herbal tea has potential as an alternative herbal beverage derived from local wisdom that may support the success of exclusive breastfeeding programs.